MONITORING SYSTEM OF THE INFORMATION AND COMMUNICATION COMPLEX OF GROUND MOBILE ROBOTIC PLATFORMS - NIKONOV, OLEH; FILIPOV, VIACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents an advanced concept of a monitoring system designed for the information and communication complex of ground mobile robotic platforms. The proposed approach is aimed at ensuring stable, secure and high-performance functioning of robotic systems that operate in dynamic, uncertain and technologically challenging environments. Ground mobile robotic platforms rely on a coordinated interaction between sensor modules, communication channels, computing units and executive components, all of which must maintain reliable operation to guarantee autonomous navigation, perception of the surrounding space and correct execution of assigned missions. In practical applications these elements are influenced by mechanical impacts, unpredictable environmental changes, electromagnetic disturbances, cyberattacks and internal failures, which significantly increases the need for an integrated monitoring and diagnostic infrastructure. The monitoring system proposed in the article unifies multi-source telemetry processing, real-time diagnostic procedures, detection of abnormal behaviour, prediction of potential failures and information security mechanisms within a single architectural framework. Special emphasis is placed on identifying critical parameters that describe the operational state of sensor systems, wireless and wired communication channels, on-board computational modules and motion control subsystems. The system incorporates intelligent diagnostic algorithms based on statistical methods, machine learning techniques and models of fuzzy logic. These methods enable early detection of hidden malfunctions, gradual degradation of components and deviations that may lead to mission failure. Furthermore, the monitoring architecture includes information protection mechanisms that ensure resistance to signal substitution, intentional distortion of navigation data, blocking of communication channels, unauthorized access attempts and other forms of external interference. The practical significance of the proposed solution is manifested in its ability to increase the autonomy, survivability and operational stability of ground mobile robotic platforms in complex or high-risk conditions. The monitoring system can be integrated into existing robotic platforms without a need for substantial modifications of their structure. It enables continuous assessment of the technical condition of key components, automatic transition to backup communication or control modes, protection of internal and external information flows and timely notification of the operator about emerging threats or failures.